THE IMPACT OF DIGITALISATION ON ECONOMIC GROWTH IN DEVELOPING COUNTRIES - Caroline Caroline (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Digitalisation has created a wave of significant change around the world, with impacts particularly felt in developing countries. This study explores how digitalisation has contributed to economic growth in these countries. Through secondary data analysis and a literature review, this study identifies the various ways in which digitalisation affects the economy, including increased access to markets, operational efficiency, and financial inclusion. The study also highlights the important role of digital infrastructure development and investment in technology education as essential supporting factors. Although the overall impact is positive, the study also recognises challenges, such as the digital divide, privacy issues and cybersecurity, which require attention through inclusive and strategic policies. The study concluded that, with the right approach, digitalisation can be a significant driving force for economic growth and social progress in developing countries, showing the potential to narrow the global gap through innovation and inclusion.